2022
DOI: 10.3748/wjg.v28.i27.3314
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between dietary patterns, obesity and nonalcoholic fatty liver disease

Abstract: The prevalence of nonalcoholic fatty liver disease (NAFLD) is rising worldwide, paralleling the epidemic of obesity. The liver is a key organ for the metabolism of proteins, fats and carbohydrates. Various types of fats and carbohydrates in isocaloric diets differently influence fat accumulation in the liver parenchyma. Therefore, nutrition can manage hepatic and cardiometabolic complications of NAFLD. Even moderately reduced caloric intake, which leads to a weight loss of 5%-10% of initial body weight, is eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 116 publications
1
10
0
Order By: Relevance
“…Since both juices attenuated hepatocellular impairment and excessive lipid droplet accumulation induced by the HFF diet, their protective effects against NAFLD could be speculated. Our findings are in line with previous studies in humans and animals which found improvement in liver steatosis and NAFLD by polyphenol-rich supplements [ 56 , 57 ]. The liver steatosis, as detected in our HFF rats, is commonly associated with hepatic inflammation, characterized by infiltration of monocyte-derived macrophages and activation of resident Kupffer cells, as well as increased proinflammatory and decreased anti-inflammatory cytokines [ 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…Since both juices attenuated hepatocellular impairment and excessive lipid droplet accumulation induced by the HFF diet, their protective effects against NAFLD could be speculated. Our findings are in line with previous studies in humans and animals which found improvement in liver steatosis and NAFLD by polyphenol-rich supplements [ 56 , 57 ]. The liver steatosis, as detected in our HFF rats, is commonly associated with hepatic inflammation, characterized by infiltration of monocyte-derived macrophages and activation of resident Kupffer cells, as well as increased proinflammatory and decreased anti-inflammatory cytokines [ 58 ].…”
Section: Discussionsupporting
confidence: 93%
“…Notably, olive oil intake, even in the absence of calorie restriction, has been shown to exhibit beneficial effects on NAFLD, even with minimal weight loss (approximately 2%) [ 30 ]. However, specific studies have reported that calorie-restricted MD interventions can lead to substantial weight loss, ranging from 5% to 10%, achieving the goals suggested by the European Association for the Study of Liver Clinical Practice Guidelines [ 8 , 58 , 59 , 60 , 61 ]. Given that the magnitude of weight loss promoted by olive oil itself is relatively small, the combination of calorie restriction and olive oil consumption emerges as a promising strategy to induce the recommended degree of weight reduction and to promote notable improvements in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of nonalcoholic fatty liver disease (NAFLD) has continued to increase over the past few decades in line with the global prevalence of obesity, with one quarter of the world's population affected in the last 5 years, with prevalence rates particularly high in Asia and the Americas [1][2] . Dietary patterns with poorly structured diets and increasing proportions of lipids for energy supply are important drivers of metabolic syndromes in individuals suffering from diseases such as obesity and NAFLD [3][4][5] . Studies have reported that high-fat diet (HFD) can indirectly cause liver damage by disrupting the gut microbiota, leading to excessive deposition of ectopic fat in hepatocytes [6][7] .…”
Section: Introductionmentioning
confidence: 99%